ELECTROCHEMICAL WASTE WATER TREATMENT - S M Nazmuz Sakib (Waste Technology, 2022)
Wastewater got much of our intention these days because wastewater is polluting our lakes, pounds and even sea have a lot of contaminated amount of waste. This water is hazardous for the acute life, dangerous for living things. Wastewater polluted the natural reservoirs. Over the past, the knowledge of the mechanisms of electrochemical wastewater treatment has progressively evolved. A comprehensive understanding of the types of methods and mechanisms of treatment of wastewater is a prerequisite to the understanding of their relativities and elucidation of intermediate products generated during the oxidation process and degradation pathways. The type, nature, and quantity of reactive species generated in electrochemical treatment processes are controlled by many factors, including the type of the treatment technique, electrode/electro catalyst materials, water/wastewater composition, water pH conditions, and operating parameters are to be considered. Multiple methods such as separation, conversion and combined methods are used for treatment. However, basic principle works on the electrochemical mechanism. This article gives the basic idea of electrochemical methods working principles, techniques being considered. It will also help us understand the by products recovery of different metal ions and how they converted into useful form. Best methods based on the efficiency and economic value. Feasibility of long term and short term methods for the treatment of wastewater.